The Abundance of coral reef fishes and associated reef fishes in the established marine sanctuary at Medano White Island, Agoho, Mambajao, Camiguin, Philippines - Apugan, Roberto S.; Paderanga, Oliver R.T. (2005)
The marine reserve at Medano White Island, Agoho, Mambajao, Camiguin, was established at one of mitigating strategies to conserve and restore the fishery resources from further degradation and depletion. The study's primary purpose is to determine and compare the abundance of fishes, found within the marine reserve and non-reserve areas, in terms of mean density and biomass, and species richness. Fish assemblages were quantitatively recorded through visual census from November 2001 through September 2002. A total of 122 species of fishes belonging to 30 families were recorded. Of the 122 species family Pomacentridae had the most number of species recorded (21 species). The existence of the marine reserve had a significant effect on the area's mean species richness, density, and biomass. The abundance of coral reef fishes found within the marine reserve was significantly greater than that found in the non- reserve areas. The occurrence of large pelagic predatory species within the reserve, particularly Elagatis bipinnulata represented a significant contribution to fish biomass. Perturbation, in the form of fishing within the reserve, drastically reduced the abundance of fish.
Keywords: Marine Protected Areas; Coral reef fisheries